HIV Reservoir Decay and CD4 Recovery Associated With High CD8 Counts in Immune Restored Patients on Long-Term ART - Zhang, Lu-Xue; Jiao, Yan-Mei; Zhang, Chao; Song, Jin-Wen; Fan, Xing; Xu, Ruo-Nan; Huang, Hui-Huang; Zhang, Ji-Yuan; Wang, Li-Feng; Zhou, Chun-Bao; Jin, Lei; Shi, Ming; et al. (Frontiers in Immunology, 2020)
Background. Whether varying CD8 counts influence on human immunodeficiency virus (HIV) reservoir and CD4 restoration in patients with CD4 ≥ 500 cells/μL after long-term antiretroviral therapy (ART) remains unknown. In this study, we analyzed relationships between CD8 levels with viral reservoir decay or CD4 recovery in immune restored patients on long-term ART. Methods. Chronic HIV-infected patients who received 5-year ART with CD4 ≥ 500 cells/μL were grouped according to CD8 counts: CD8 <500 (Group1), 500-1000 (Group2) and ≥1000 cells/μL (Group3). CD4 recovery, viral decay, CD8 T-cells function and their correlations were analyzed during ART among the three groups. Results. Dynamics of viral decay and CD4 recovery were different among the three groups. Both viral decay and CD4 recovery were higher in Group3 than other two groups after 5-year of ART, mainly during years 3-5 of ART. Higher Ki67 and lower PD-1 expressed on CD8 T-cells in Group3 compared with the other groups, and Group3 showed stronger CD8 T-cells functional capacity after 3-year of ART. Reduced HIV DNA levels and increased CD4 counts between years 3-5 of ART were positively correlated with CD8 counts and function. Conclusions. High CD8 counts are beneficial for persistent viral decay and CD4 recovery in immune restored patients during long-term ART.